Pengembangan Video Pembelajaran Berbasis Sentra Balok untuk Meningkatkan Numerasi Anak Usia Dini - Purwanti, Indah; Buchori, Achmad; Siswanto, Joko (Universitas PGRI Semarang, 2025)
This study aims to describe the validity of block center-based learning videos to improve the numeracy skills of early childhood, analyze the practicality of block center-based learning videos to improve the numeracy skills of early childhood, describe the effectiveness of block center-based learning videos to improve the numeracy skills of early childhood. The subjects of the study were students in the 4-5 year age group used, namely 20 children at Tarbiyatul Athfal II Kawak Kindergarten, Pakis Aji District, Jepara Regency, taken at the beginning of the 2022/2023 school year. This study uses the ADDIE model approach (Robert Maribe Branch., 2022) which consists of 5 steps, namely analyze, design, develop, implement and evaluate. The research methods used are questionnaires, observation sheets and documents. The conclusion obtained is: Based on the results of the analysis of the Material Expert observation score data, it is proven that the block center-based learning video from the Material aspect is at a level of 94.23% in the very valid category, from the media aspect at a level of 93.33% in the very valid category. Based on the results of the teacher perception score analysis, it is proven that the block center-based learning video at an average level of 96.05% is in the very practical category and based on the perception of the child's parents an average of 88.75% is in the fairly practical category. The effectiveness of the block center-based learning video to improve numeracy literacy skills for kindergarten children based on the N Gain test, T Test, and Cohen D Test: (1) based on the results of the N Gain test, an average increase in gain of 0.56 (56%) was obtained, meaning that the increase in numeracy literacy ability scores was in the fairly effective category in the interval 56 - 75; (2) based on the t-test, the calculated t was 10.614 t-table (2.093), meaning that there was a significant difference in the numeracy literacy ability scores before and after treatment; (3) based on the Cohen d effectiveness test, it was 1.972 and the effect size was 0.702, with relatively moderate effectiveness (0.5 - 0.7 + is a moderate effect) meaning that the block center-based learning video had a relatively moderate effectiveness in improving the block center-based numeracy literacy abilities of early childhood children.